Characteristics of young people with long term conditions close to transfer to adult health services. Issue 1 (June 2015) - Merrick, Hannah; McConachie, Helen; Le Couteur, Ann; Mann, Kay; Parr, Jeremy; Pearce, Mark; Colver, Allan
Abstract Background For many young people with long term conditions (LTC), transferring from paediatric to adult health services can be difficult and outcomes are often reported to be poor. We report the characteristics and representativeness of three groups of young people with LTCs as they approach transfer to adult services: those with autism spectrum disorder with additional mental health problems (ASD); cerebral palsy (CP); or diabetes. Methods Young people aged 14 years-18 years 11 months with ASD, or those with diabetes were identified from children's services and those with CP from population databases. Questionnaires, completed by the young person and a parent, included the 'Mind the Gap' Scale, the Rotterdam Transition Profile, and the Warwick and Edinburgh Mental Wellbeing Scale. Results Three hundred seventy four young people joined the study; 118 with ASD, 106 with CP, and 150 with diabetes. Participants had a significant (p  < 0.001) but not substantial difference in socio-economic status (less deprived) compared to those who declined to take part or did not respond. Condition-specific severity of participants was similar to that of population data. Satisfaction with services was good as the 'gap' scores (the difference between their ideal and current care) reported by parents and young people were small. Parents' satisfaction was significantly lower than their children's (p  < 0.001). On every domain of the Rotterdam Transition Profile, except for education and employment, significant differences were found between the three groups. A larger proportion of young people with diabetes were in a more independent phase of participation than those with ASD or CP. The wellbeing scores of those with diabetes (median = 53, IQR: 47–58) and CP (median = 53, IQR: 48–60) were similar, and significantly higher than for those with ASD (median = 47, IQR: 41–52;p  < 0.001). Conclusions Having established that our sample of young people with one of three LTCs recruited close to transfer to adult services was representative, we have described aspects of their satisfaction with services, participation and wellbeing, noting similarities and differences by LTC. This information about levels of current functioning is important for subsequent evaluation of the impact of service features on the health and wellbeing of young people with LTCs following transfer from child services to adult services.